2016
DOI: 10.3892/or.2016.5092
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-330-5p negatively regulates ITGA5 expression in human colorectal cancer

Abstract: Colorectal cancer (CRC), one of the most prevalent malignant cancers, has high rates pf incidence and is the fourth leading cause of cancer-related deaths for both men and women worldwide. MicroRNAs (miRNAs) play critical roles in the development of various types of cancers. miRNA‑330-5p has been implicated in the progression of prostate, neuronal and pancreatic cancers by regulating proliferation, migration, invasion and epithelial-mesenchymal transition of cells. The purpose of the present study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 26 publications
5
43
0
Order By: Relevance
“…Indeed, miR-330-5p is also identified to be a credible binding site in the E2F1 mRNA sequence [43]. Yoo et al reported that downregulated miR-330-5p expression can affect colorectal cancer development [40]. Bibby and colleagues observed an increase in radioresistance due to miR-330-5p silencing, suggesting that the downregulation of miR-330-5p in tumors can alter the response to radiotherapy in esophageal adenocarcinoma [42], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, miR-330-5p is also identified to be a credible binding site in the E2F1 mRNA sequence [43]. Yoo et al reported that downregulated miR-330-5p expression can affect colorectal cancer development [40]. Bibby and colleagues observed an increase in radioresistance due to miR-330-5p silencing, suggesting that the downregulation of miR-330-5p in tumors can alter the response to radiotherapy in esophageal adenocarcinoma [42], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…Promising roles of miRNA in carcinogenesis have been shown to be closely related to the epithelial-mesenchymal transition, cancer stem cell properties, tumor metastasis initiation and response to radiotherapy or chemotherapy [38]. The altered expression of miR-330 has been found in the carcinogenesis of various tumors [39,40]. The present study sought to investigate miR-330 expression in patients with BM from LC following conventional wholebrain radiation and the role of miR-330 in radiation sensitivity and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K also contributes to the progression of atherosclerosis through affecting vascular endothelial cells, using a variety of signals can be transduced and regulated through the PI3K-Akt signaling pathway. Regulation of this pathway can directly or indirectly promote the pathological progression of atherosclerosis (9). In the present study, it was observed that Gambogic acid treatment significantly induced PI3K, p-Akt, p-mTOR and p-p70S6K1 protein expression in AAA mice.…”
Section: Discussionsupporting
confidence: 56%
“…It specifically binds to the phosphatidylinositol base and transfers the phosphate group of ATP to phosphorylate PI into inositol lipids (8). Lymphokine-activated killer T-cell-originated protein kinase (PBK) forms an important signaling pathway, termed the PI3K-protein kinase B (Akt) signaling pathway, which together with Akt, located in its downstream, serves an important role in the survival, differentiation, proliferation and apoptosis of cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR‐330‐5p has been identified as an important regulator of multiple physiological and pathological processes in mammals. In humans, downregulation of miR‐330‐5p expression may affect colorectal cancer development via modulation of integrin α5 (ITGA5) expression (Yoo, Kim, & Yoon, ). MiR‐330‐5p‐mediated regulation of SRPR is needed for the regulation of proliferation of epidermal keratinocytes in mice (Kim, Yoo, Choi, Lee, & Yoon, ).…”
Section: Discussionmentioning
confidence: 99%